2021
DOI: 10.1002/jib.670
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced susceptibility of alcohol‐free and low alcohol beers to microbiological spoilage: implications for draught dispense

Abstract: The spoilage of six alcohol-free (AFB, ≤ 0.05% ABV) and two low alcohol beers (LAB, ≤ 1.2% ABV) was assessed by challenge testing with microflora from draught beer. Spoilage of AFB and LABs was greater (2-5 x) than two 'control' premium lager beers (4.5% ABV). Measurement of spoilage by challenge testing was reproducible irrespective of the source of draught beer microflora (public house, date, or beer style). Spoilage was correlated with the level of 'fermentables' (glucose + fructose + maltose) in the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies assessing the susceptibility of NoLo beers to spoilage have been limited to those identifying effective pasteurisation strategies and the unsurprising observation that ethanol augments heat in killing microorganisms. Experiments using spoilage yeasts ( Quain, 2021 ), yeast spores ( Rachon et al, 2021 ), and bacteria ( Adams et al, 1989 ; L'Anthoën and Ingledew, 1996 ) have all demonstrated that microbes are more tolerant to heat when alcohol is absent. Thus, NoLo beers in final pack may necessitate enhanced levels of pasteurisation to reach commercial stability than standard beers containing alcohol.…”
Section: Microbiological Opportunities and Challenges For No- And Low...mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies assessing the susceptibility of NoLo beers to spoilage have been limited to those identifying effective pasteurisation strategies and the unsurprising observation that ethanol augments heat in killing microorganisms. Experiments using spoilage yeasts ( Quain, 2021 ), yeast spores ( Rachon et al, 2021 ), and bacteria ( Adams et al, 1989 ; L'Anthoën and Ingledew, 1996 ) have all demonstrated that microbes are more tolerant to heat when alcohol is absent. Thus, NoLo beers in final pack may necessitate enhanced levels of pasteurisation to reach commercial stability than standard beers containing alcohol.…”
Section: Microbiological Opportunities and Challenges For No- And Low...mentioning
confidence: 99%
“…This poses an additional level of complexity, since the quality of beer once it has left the brewery is no longer under the control of the brewer but is dictated by handling procedures at the point of dispense ( Mallett and Quain, 2019 ). A series of challenge-test studies performed by Quain (2021) demonstrated that draught beer spoilage was 2–5 times greater in NoLo lager type beer when compared to standard products at 4.5%. Interestingly, spoilage was strongly correlated with the levels of residual fermentable sugars and the availability of micronutrients in the product, rather than the absence/presence of ethanol per se .…”
Section: Microbiological Opportunities and Challenges For No- And Low...mentioning
confidence: 99%
See 2 more Smart Citations